The Implications of Khalwat Offence on Youth in Brunei Darussalam - Haji Marali, Siti Nurmunirah; Mahmud, Dr. Hafini (Sharia Journal and Education Center Publishing, 2024)
Khalwat is a moral offence and one of the Sharia criminal offences which is considered to be a 'mukaddimah zina'. The provisions and penalties have been stated under the Perintah Kanun Hukuman Jenayah Syariah (PKHJS 2013) of Brunei Darussalam. However, if examined based on statistics, the number of khalwat cases seems to be increasing every year, showing that Brunei Darussalam is not immune from social problems that result in a moral crisis in society. Therefore, this article aims to explore the consequences that will be faced by the youth as a result of committing khalwat offence. The research method adopts a qualitative approach through case studies using interview methods and document analysis. The results of the study found that on average, this offence were committed by Muslim youths or teenagers as well as non-Muslims. In fact, the impact of committing this khalwat offence also has a more negative impact on the future of the youth. As a recommendation, this study suggests the need for improvement of legal agencies in providing exposure programmes to the community on an ongoing basis, and the community also plays the most important role in emphasizing the manners of association with different genders.